Adult-Onset Leukoencephalopathy with Brain Stem and Spinal Cord Involvement and Normal Lactate: Case Report - Özdem Ertürk; Cengiz Yalçınkaya; Aksel Siva; Marjo S van der Knaap (Türk Nöroloji Dergisi, 2010)
Leukoencephalopathy with brain stem and spinal cord involvement and high lactate (LBSL) is a recently described leukoencephalopathy with a genetically proven underlying defect. Clinical features are slowly progressive pyramidal, cerebellar and dorsal column dysfunction with childhood or rarely adult onset. The genetic basis of the disease was recently identified, which concerned mutations in the DARS2 gene encoding mitochondrial aspartly-tRNA synthetase. The disease has distinct magnetic resonance imaging findings including inhomogeneous cerebral white matter abnormalities and selective brain stem and spinal cord tract involvement. Additionally, there are usually increased lactate levels on magnetic resonance spectroscopy (MRS) of the abnormal white matter. In this case report, we describe the clinical and radiological features of a patient with genetically proven adult-onset LBSL and normal lactate levels on MRS